Induced charge effects on electrokinetic entry flow - Prabhakaran, Rama Aravind (2017)
Electrokinetic flow, due to a nearly plug-like velocity profile, is the preferred mode for transport of fluids (by electroosmosis) and species (by electrophoresis if charged) in microfluidic devices. Thus far there have been numerous studies on electrokinetic flow within a variety of microchannel structures. However, the fluid and species behaviors at the interface of the inlet reservoir (i.e., the well that supplies the fluid and species) and microchannel are still largely unexplored. This work presents a fundamental investigation of the induced charge effects on electrokinetic entry flow due to the polarization of dielectric corners at the inlet reservoir-microchannel junction. We use small tracing particles suspended in a low ionic concentration fluid to visualize the electrokinetic flow pattern in the absence of Joule heating effects. Particles are found to get trapped and concentrated inside a pair of counter-rotating fluid circulations near the corners of the channel entrance. We also develop a depth-averaged numerical model to understand the induced charge on the corner surfaces and simulate the resultant induced charge electroosmosis (ICEO) in the horizontal plane of the microchannel. The particle streaklines predicted from this model are compared with the experimental images of tracing particles, which shows a significantly better agreement than those from a regular two-dimensional model. This study indicates the strong influences of the top/bottom walls on ICEO in shallow microchannels, which have been neglected in previous two-dimensional models.